Analysis of the Use of Second Instagram Accounts for Self Presentation among Female Students at Universitas Muhammadiyah Surakarta - Aghisna Ayu Kustifah; Rina Sari Kusuma (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study explores the use of second Instagram accounts as a medium for self-presentation among female students at Muhammadiyah University of Surakarta. It examines how female students utilize second accounts to manage their online identities and social interactions. Methodology: This study employed a descriptive qualitative approach. Data were collected through observation and in-depth interviews with female students aged 20–25 years who actively use second Instagram accounts for self-presentation. The study is grounded in Erving Goffman's Dramaturgical Theory, which conceptualizes social life as a performance involving front-stage and back-stage behaviors. Findings: The findings reveal that female students use second Instagram accounts as both front-stage and back-stage spaces. As a front stage, second accounts are carefully managed to present a favorable image to a specific audience. As a back stage, these accounts provide greater freedom for self-expression. The study also identifies several motivations for creating second accounts, including avoiding social judgment, expressing themselves more freely, monitoring others' activities, and filtering friendships. Applications/Originality/Value: This study highlights the significant role of second Instagram accounts in providing a safer and more private space for female students to express their identities and share aspects of their lives that may not be considered appropriate for public display on their primary accounts. These findings contribute to a broader understanding of digital selfpresentation practices among young adults in the context of social media.